2003
DOI: 10.1248/cpb.51.815
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Poly(ethylene glycol) (PEG) Chain Length of PEG-Lipid on the Permeability of Liposomal Bilayer Membranes

Abstract: The effects of poly(ethylene glycol) (PEG) chain length of PEG-lipid on the membrane characteristics of liposomes were investigated by differential scanning calorimetry (DSC), freeze-fracture electron microscopy (FFEM), fluorescence polarization measurement and permeability measurement using carboxyfluorescein (CF). PEG-liposomes were prepared from mixtures of dipalmitoyl phosphatidylcholine (DPPC) and distearoyl phosphatidylethanolamines with covalently attached PEG molecular weights of 1000, 2000, 3000 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 20 publications
4
40
0
Order By: Relevance
“…This shows that the fluidity of the liposomal bilayer membrane is not the main factor in CF leakage from PEG-liposomes which consist of this lipid composition. In our previous paper, 7) we confirmed that the addition of DSPE-PEG to the DPPC liposomal bilayer membrane causes lateral phase separation in the gel and liquid-crystalline states, as seen by DSC measurements and freeze-fracture electron microscopy observations. Solute leakage from liposomes rapidly accelerates when the components which constitute the liposomes cause phase separation.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…This shows that the fluidity of the liposomal bilayer membrane is not the main factor in CF leakage from PEG-liposomes which consist of this lipid composition. In our previous paper, 7) we confirmed that the addition of DSPE-PEG to the DPPC liposomal bilayer membrane causes lateral phase separation in the gel and liquid-crystalline states, as seen by DSC measurements and freeze-fracture electron microscopy observations. Solute leakage from liposomes rapidly accelerates when the components which constitute the liposomes cause phase separation.…”
Section: Resultssupporting
confidence: 83%
“…In general, when the solute leakage from the liposomes is discussed, differences in the liposomal bilayer thickness and particle sizes should be taken into consideration. 15) In our previous study, 7) we confirmed that the addition of DSPE-PEG to the DPPC liposomal bi- layer membrane caused lateral phase separation, and it seems that the thickness of liposomal bilayer membranes is not uniform. Furthermore, it is necessary to calculate the liposomal bilayer thickness for PEG-liposomes considering the thickness of the PEG chain layer on the liposomal surface.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Furthermore, the reason why PEG-lipids localize to the edge portion of the disk micelle was considered. In our previous paper, 11) we confirmed that the addition of PEG-lipid to the DPPC liposomal bilayer membrane caused lateral phase separation, as seen by freeze-fracture electron microscopic observation. Bedu-Addo et al 21) suggested that the occurrence of the phase separation in the PEG-liposomes due to the property of the PEG chain of the PEG-lipid, that is, the phase separation of the PEG-liposome, is generated by the PEG chain-chain entanglement due to the van der Waals forces, and also inter-and intra-chain hydrogen bonds that act in the PEG chains.…”
Section: Calorimetry and Cryo-transmission Electron Microscopic Studisupporting
confidence: 83%
“…The effect of PB-PEO on vesicle permeability is reminiscent of the effect that PEG-ylation exerts on the self-assembly and permeability of liposomes [30][31][32][33]. It was observed that addition of increasing concentrations of DSPE-PEG (DSPE: distearoylphosphatidylethanolamine; M W(PEG) > 2000) decreases the CF permeability of the PEG-ylated liposomes [32].…”
Section: Encapsulation Efficiency and Membrane Permeabilitymentioning
confidence: 99%